Improving musculoskeletal fitness and the performance enhancement of basketball skills through neuromuscular training program - Ahmed, T. (Journal of Human Sport & Exercise, 2015)
The purpose of this study was to evaluate the effect of eight weeks of neuromuscular training program (NMTP) on musculoskeletal fitness and performance enhancement for basketball players. Twenty four male basketball players participated in this study and were divided into neuromuscular training group (NMT) or control group (CON). All players trained together as a team where NMT group participated 8 weeks of NMTP three times a week and CON group followed their regular protocol as guided by their coach. Musculoskeletal fitness was evaluated based on muscular strength, muscular endurance, and flexibility. Muscle strength was assessed by measuring grip strength and vertical jump test, muscular endurance was measured by push-up test and sit- up test, and flexibility was assessed using the sit-and-reach test. The basketball skills were assessed by passing test, speed spot shooting test, dribbling test, and defensive skill test. The subjects underwent all of the previously described tests before and after the training program. The results showed that the two groups demonstrated significant improvement, but the greater percentage of change is found in NMT group. The percentage of improvement in musculoskeletal fitness was ranged between 17% to 47% for NMT group versus 5% to 13% for CON, while ranged between 18% to 30% for NMT group versus 10% to 17% for CON group in skills performance. The study demonstrated that there is a significant effect of the NMTP which focused on core stability and lower extremity strength on musculoskeletal fitness and skills performance for young male basketball players